Design Study for Optimum Multivariable Control System for Wind Tunnel Regulation - Ashour, Ashraf Hussein (2016)
This Dissertation investigates the design of a multivariable control system for a wind tunnel to obtain the optimum control strategy in order to minimize energy dissipation, noise and cost which improve the quality and integrity of the wind tunnel test measurements. First the research is focused on identifying how a wind tunnel work with brief information about its components and types. Then the least effort control technique will be applied and discussed. Also study includes a controller designed by the Nyquist Array method and other control strategies. Plots of step response, disturbance suppression and transient recovery for both techniques will be presented with their block diagrams. The dissertation concludes with a comparison of the control methods used, based on the performance and energy dissipation.